Multidimensional poverty measurement and analysis : chapter 4 - counting approaches: definitions, origins and implementations - Alkire, S; Foster, J; Seth, S; Santos, M; Roche, J; Fernandez, P (2015)
The measurement of poverty involves identification: the fundamental step of deciding who is to be considered poor. A ‘counting approach’ is one way to identify the poor in multidimensional poverty measurement, which entails the intuitive procedure of counting the number of dimensions in which people suffer deprivation. Atkinson (2003) advised an engagement between multidimensional measures from social welfare and the counting approaches due to the widespred policy use of the latter. This chapter reviews applications of the counting methods in the history of poverty measurement. We focus on empirical studies since the late ‘70s which developed relatively independently of each other in two regions. In Latin America, applications of the Unsatisfied Basic Needs Approach were widespread, often using census and survey data. European work drew on concepts of social exclusion and inclusion, and now include national and European intiatives.